Estudo de genes da Via Wnt e sua associacao com o Transtorno Afetivo Bipolar - Simone Becho de Campos (2013)
Bipolar Disorder (BD) is a severe and chronic psychiatric illness with progressive increase in the severity of episodes. The prognosis for patients with BD is poor, with high rates of relapse in residual symptoms, cognitive impairment and decreased quality of life. A growing body of research supports the assumption that BD arises from abnormalities in neuronal plasticity. Several lines of evidence suggests that the Wnt family is involved in this pathway since it is related to key developmental processes such as cell growth, migration and cell differentiation. Therefore, the aim of our study was to evaluate whether genes of the Wnt pathway are associated to BD and its comorbidities. Our sample consisted of 546 individuals: 306 patients with BD and 240 healthy controls. We used the genes WNT2B, WNT3A, WNT5A, WNT7A, APC1 and FZD3. We found no correlation between the studied tagSNPs and BD. However, we found a positive association between ACP1 tagSNP, rs7419262, and violent suicide attempt, and between the WNT2B tagSNPs, rs3790606 and rs351372, and generalized anxiety disorder as a comorbidity in patients with BD. We conclude that the Wnt pathway may be associated with susceptibility to BD and suicide.